Key Points of Compaction Construction Technology for Roadbed and Pavement in Highway Engineering - Gou, Shicai; Zeng, Caifan; Lin, Xiaoming (Journal of Theory and Practice of Management Science, 2023)
In recent years, China has constructed various scale and level of road projects. The implementation of these projects has improved China's road transportation system and brought great convenience to people's travel. However, the implementation of roadbed and pavement compaction is an aspect that cannot be ignored in road engineering. The application of technology and construction effectiveness are related to the quality of road engineering. Therefore, in any road engineering project, standardized roadbed and pavement compaction must be carried out based on the construction requirements of the road itself to ensure that the compaction meets the construction requirements. Based on this, the article focuses on the key points of roadbed and pavement compaction technology in road engineering, which has certain guiding value for road engineering construction.